1996
DOI: 10.1177/0002716296546001007
|View full text |Cite
|
Sign up to set email alerts
|

News Frames, Political Cynicism, and Media Cynicism

Abstract: Public confidence in Congress, the government, and social institutions has reached new lows. Healthy skepticism may have given way to corrosive cynicism. Some media watchers and critics blame the media for their preoccupation with the game and strategy of politics rather than social problems and their solution. Others deny that changes in news have affected the quality of democracy or the depth of political alienation. Studies that we have conducted over the past four years show that subtle changes in the way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(154 citation statements)
references
References 7 publications
2
137
0
13
Order By: Relevance
“…For example, research in the US and UK has found it to be strongly influenced by political media campaigns (e.g. Cappella & Jamieson, 1996;Vreese & Elenbaas, 2008), and it appears to have a complex relationship with voting behavior, interacting with variables such as the social status of one's group and the perception of opportunity for political change (Southwell & Pirch, 2003). Interest in politics and political cynicism are, therefore, distinct constructs that have different consequences for political involvement (Bynner & Ashford, 1994;Henn, Weinstein, & Wring, 2002).…”
Section: Four Varieties Of Education Effectmentioning
confidence: 99%
“…For example, research in the US and UK has found it to be strongly influenced by political media campaigns (e.g. Cappella & Jamieson, 1996;Vreese & Elenbaas, 2008), and it appears to have a complex relationship with voting behavior, interacting with variables such as the social status of one's group and the perception of opportunity for political change (Southwell & Pirch, 2003). Interest in politics and political cynicism are, therefore, distinct constructs that have different consequences for political involvement (Bynner & Ashford, 1994;Henn, Weinstein, & Wring, 2002).…”
Section: Four Varieties Of Education Effectmentioning
confidence: 99%
“…Examples of such attributes are a hazard's adverse effects on children, its fatal consequences, and disagreement or uncertainty among scientific experts about the nature of the risk. [32][33][34] Conversely, portrayal of a risk as having been deliberately exaggerated by politicians, scientists or the media may increase scepticism among the public as to the true importance of the issue and result in decreased levels of concern. 35,36 The 2009 outbreak of swine flu was accompanied by extensive reporting by the UK news media.…”
Section: Introductionmentioning
confidence: 99%
“…Election coverage frames identified by Cappella and Jamieson (1996) were adapted to assess if there is evidence of gender differences in how and Personal Attributes Questionnaire (PAQ, see Spence, Helmreich, & Stapp, 1975), two widely used social psychology measurements of the femininity-masculinity dimension, were employed as tools to conceptualize existing election frames as gendered or gender neutral. It is important to note here that the relative masculinity, femininity, and gender neutrality of candidates are not of interest as much as the reporter's employment of frames that signal gender neutrality or genderedness in reporting.…”
Section: Gender In Election Reportagementioning
confidence: 99%